Numerical Analysis of SHB Effects in Laterally-Coupled Distributed Feedback (LC-DFB) Lasers - Seifouri, M.; Shahshahani, F.; Faraji, A. (Engineering, Technology & Applied Science Research, 2012)
In this paper the stability of Laterally-Coupled Distributed Feedback (LC-DFB) Lasers against the Spatial Hole Burning (SHB) effect is analyzed theoretically. The stability of the laser structure is evaluated using the flatness parameter F. It is shown that the LC-DFB lasers are stable in a wide range of different values ​​of ridge width and amplitude grating. The stability is sustained with increasing injection current. The results show that the flatness parameter is minimal for certain values ​​of the amplitude grating. The numerical calculations have been done by coupled wave and carrier rate equations on the basis of the transfer matrix method (TMM)